2014
DOI: 10.15314/tjse.201428109
|View full text |Cite
|
Sign up to set email alerts
|

Influence of physical activity on students physical self-concept and satisfaction with life: Physical and non-physical education students perspective

Abstract: The purpose of this study was to find out the physical and non-physical education students' physical self-concept and satisfaction with life. 470 students were selected randomly as two sample groups (physical and non-physical education students). The valid sample of study was 449. The two questionnaires employed here were the Physical Self-Description Questionnaire (PSDQ-S) and the Satisfaction with Life Scale. SPSS 20 was used to produce the Mean; Standard Deviations; Pearson's Product Moment Correlation (r);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Furthermore, our study also showed a positive relationship between physical activity level and satisfaction with life. This is in line with previous studies where this relationship was also observed [ 65 , 66 , 67 ].…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, our study also showed a positive relationship between physical activity level and satisfaction with life. This is in line with previous studies where this relationship was also observed [ 65 , 66 , 67 ].…”
Section: Discussionsupporting
confidence: 94%
“…The subjective quality of life domain measures correlated most strongly with general life satisfaction-correlation ranged from 0.16 to 0.65 in the study of [98]. Generally speaking, the findings of [35] study indicated that physical activity has an effect on positive physical self-concept and life satisfaction. The study of [99] revealed relationships between perceived life dissatisfaction and noninvolvement in physical activity.…”
Section: Discussionmentioning
confidence: 72%
“…In various parts of the world, the authors have shown significantly higher life satisfaction in people participating in physical and sporting activities than in people who did not practice physical and sporting activities [in Turkey and in Germany [34]; in Turkey [35]; in Slovakia [36,37]; in Sweden [38]; in Taiwan [39]; in America [40,41]; in Poland [42]; in Spain [43]].…”
Section: Sport For the Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…According to Mehdinezhad and Golsanamlou (2014), self-concept refers to the individual's assessment of his or her qualifications, attributes, and features that are comparable with others. There are different types of self-concept and one of which is physical self-concept.…”
Section: Introductionmentioning
confidence: 99%